Answer:
x = -42 and y = -73
Explanation:
Given equations are :
y-x = -31 eq(1) and
-4x+3y = -51 eq(2).
We solve it by eliminating by y and then putting the value of x into the equation.
From eq(1) ,we get
y = -31+x eq(3)
Putting above equation in eq(2) , we get
-4x+3(-31+x) = -51
Simplifying
-4x-93+3x = -51
Adding like terms,we get
-x-93 = -51
Adding 93 to both sides of above equation,we get
-x-93+93 = -51+93
-x+0 = 42
x = -42
putting the value of x in eq(3) , we get
y = -31-42
y = -73
Hence, the solution of this system on linear equation is (-42,-73).